PEMETAAN SITUASI DUSUN BANYURIPAN DESA BANYURIPAN KECAMATAN BAYAT KABUPATEN KLATEN PROPINSI JAWA TENGAH - , LULU FADLILAH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The final task is to explain about the work of measuring and mapping land that produces the spatial information of the surface of the earth. Spatial Informa is then processed and presented in the form of a map. Work carried out so as to form a map of the control framework include measurement of horizontal, vertical measurement control framework, as well as detailed measurements and digital imaging situations. From this work resulted in a map with a scale of 1:500 situation in UTM projection system (Universal Transverse Mercator) are present spatial information of the earth's surface Banyuripan Hamlet, Village Banyuripan, District Bayat, Klaten, Central Java Province.